Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

A synergistic perovskite-transition metal carbide hybrids for high-performance supercapacitors - Zulfqar Ali Sheikh; Sayed Zafar Abbas; Dhanasekaran Vikraman; Shahzaib Ali; Doyoung Byun; Pranav K. Katkar; Naesung Lee; Sajjad Hussain; Jongwan Jung (Chemical Engineering Journal, 2026)

Mitigating chromium toxicity and enhancing rice productivity in chromium-affected regions of Odisha, India - Dibakar Ghosh; Sayed Islam; Madhumita Das; K. Laxminarayana; Ashis Maity; Ankita Jha; Partha Debroy; S. K. Jena; Arjamadutta Sarangi (Paddy and Water Environment, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Type 2 Diabetes-Induced Molecular and Functional Impairment of Adipose Tissue-Derived Mesenchymal Stromal Cells (ASCs) and Interferon Gamma Priming for Enhanced Diabetic ASC-Based Therapy - Alaa Zeinhom; Ammar Y. Mohamed; Nahla N. Abdel-Aziz; Mostafa Sayed Diab; Amir M. H. Salem; Noha N. Yassen; Eman E. A. Mohammed; Amal M. Mohamed; Ola M. Eid; Shymaa H. Hussein; Marwa Farid; Engy K. Tharwat; et al. (Stem Cell Reviews and Reports, 2026)

Techno-Economic Analysis of Microalgal Biofuels: Evaluating Cost Competitiveness Through Biotechnology Advancements - Tareq Kareri; Aman Khan; Muhammed K. Alhassan; Sedky H. A. Hassan; Mohammed Jalalah; Fahad M. Almutairi; El-Sayed Salama (International Journal of Environmental Research, 2026)

Migration and migratory connectivity of Greater Spotted Eagles (Clanga clanga) wintering at the head of the Arabian Gulf - Michael J. McGrady; Omar Al Sayed Omar; Rashed Al Hajji; Matthias Schmidt; Madan K. Oli (Journal of Ornithology, 2026)

Purification and Preliminary Characterization of an Agarase Enzyme by Marine Bacterium Aquabacterium citratiphilum EGDA30 - Zeinab A. Baleta; Mohamed I. Abou-Dobara; Ahmed K. A. El-Sayed (Current Microbiology, 2026)

Artificial spawning of African catfish (Clarias gariepinus) with different forms and sources of pituitary gland extract: influence on fecundity, sex hormones, and reproductive performance - Hala S. Khalil; Hamed H.E. Saleh; El-Sayed I. Attia; Asmaa M. El-Agri; Fatma Ragab Abouel Azm; Gad H.G. Hussein; Rasha K. Abdel-Wahed (Frontiers in Marine Science, 2026)
Introduction The investigation was performed to compare the influence of using different pituitary gland extract types (dried and fresh) from common carp ( Cyprinus carpio ) and African catfish ( Clarias gariepinus ) on fecundity, sex hormones, and artificial spawning performance of African catfish. Methods Pituitary glands were collected from sixty-four male catfish and sixty-four carp broodstocks to formulate four treatments: dried catfish pituitary gland extract (DPG catfish ), fresh catfish pituitary gland extract (FPG catfish ), dried carp pituitary gland extract (DPG carp ), and fresh carp pituitary gland extract (FPG carp ). Sixteen ripe females (920 to 1190 g) and sixteen ripe males (1060 to 1150 g) with a sex ratio (1:1 male ♂: female ♀) were chosen for each treatment. Results and discussion The highest fecundity and reproductive performance were observed in the DPG catfish -treated group, followed by the DPG carp -treated group. The latency periods were recorded as 12 h for DPG catfish , 17 h for FPG catfish , 12.5 h for DPG carp , and 21 h for FPG carp . DPG catfish treatment significantly improved (P ≤ 0.05) ovulation performance, reproductive output, fertilization and hatching success, and circulating estrogen, progesterone, and testosterone levels. In contrast, both fresh pituitary treatments (catfish and carp) resulted in noticeably lower outcomes. The results indicate that DPG catfish extract consistently outperformed other treatments across all measured spawning parameters, suggesting its effectiveness in enhancing seed production in African catfish aquaculture.

Mitigating surface industrial heat island effects in arid environments: A machine learning approach to sustainable planning - Islam M. Hamdi; Eman Albalawi; Elsayed K. AbdAlmapoed; Sayed R. AbdElaal (Energy and Buildings, 2026)

Perindopril and L‑arginine protect against arsenic trioxide–induced neurotoxicity via Keap1/Nrf2/HO‑1 activation and suppression of neuroinflammation and apoptosis - Basel A. Abdel-Wahab; Ahmed M. Abd-Eldayem; Ehab A. M. El-Shoura; Saad Misfer; Ahmed A. N. Ahmed; Eman K. Rashwan; Hend Mostafa Selim; El-sayed Gawesh; Olfat E. Mostafa; Sabrin A. Abdel Wahab; Rania A. Gad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Repurposing alogliptin for ulcerative colitis: involvement of MicroRNAs, anti-inflammatory, and barrier-restoring mechanisms - Meshal Awadh Ghayeb Alenezi; Mohamed Gamal El-Din Ewees; Elsayed K. El-Sayed; Engy M. El Morsy; Mohamad Elbaz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Deploying bacteriophage combinatorial therapy to eradicate resistant Klebsiella pneumoniae UTIs: innovative and personalized phage therapy - Usamah Sayed; Waleed K. Abdulsahib; Wael Waleed Mustafa; H. Malathi; Rajashree Panigrahi; Y. Swarna Latha; Vipasha Sharma; Aashna Sinha; Nigina Khalikova (Archives of Microbiology, 2026)

Structurally-controlled radioactive and rare metal mineralizations associated with potassic alteration in Umm Ara granitoids, southern Eastern Desert, Egypt: Implications from remote sensing, whole-rock chemistry, and geophysical data - Adel Fathy; Mokhles K. Azer; Abdelhalim S. Mahmoud; Farouk Sayed; Ahmed A. Masoud; Faris A. Abanumay (Journal of Geochemical Exploration, 2026)

Phytochemical characterization, bioefficacy, and economic potential of seaweed tannin-based emulsifiable concentrates for cotton pest management - K. Madasamy; K. Sahayaraj; Lamya Ahmed Alkeridis; Lalia A. Al-Shuraym; Hosny H. Kesba; Hanan M. A. Hamada; Samy M. Sayed (Journal of Applied Phycology, 2026)

Developmental and neurobehavioural toxicity of per- and polyfluoroalkyl substances in aquatic organisms: mechanistic insights from molecular disruption to behavioural dysfunction - Mohamed Hamed; Mohamed Abbas; A K M Munzurul Hasan; Shimaa M. Kteeba; Hesham Taher; Mohammed Abdel-Wahab; Rashad E.M. Said; Zeinab Bakr; Douglas P. Chivers; Jae-Seong Lee; Alaa El-Din H. Sayed (Aquatic Toxicology, 2026)

Pimenta racemosa extract ameliorates chemically induced ulcerative colitis in rats by suppressing inflammation and oxidative stress - Haitham A. Ibrahim; Fathia S. Elshaarawy; Mohamed I. S. Abd-elhady; Wafaa Hamdy; Merhan E. Ali; Asmaa A. Ahmed; Elsayed K. El-Sayed (Inflammopharmacology, 2026)
Pimenta racemosa ( P. racemosa ) tree leaves are used in traditional medicine to alleviate flatulence and gastrointestinal disorders. Ulcerative colitis (UC) is a gastrointestinal inflammatory disease with well-known inflammatory and immunoregulatory pathological features. The complexity of the disease requires multi-targeted treatment. Because of their relative safety and effectiveness, natural products can be utilized as adjunct and alternative agents to conventional UC treatment. So , the present work aimed to isolate phenolic constituents of the plant’s 80% aqueous methanol extract (AME) and evaluate its protective effect on acetic acid-induced ulcerative colitis (UC) in rats. The defatted AME was chromatographed, and structures of the isolated compounds were elucidated using UV, NMR spectroscopy and HPLC–ESI–MS analysis. Induction of ulcerative colitis was done using Acetic acid, the protective effect against ulcerative colitis was supported by histopathological and immunohistochemical examinations. The isolated compounds are Kaempferol 3- O - β -D-glucopyranoside (kaempferol 3- O -glucoside) or (Astragalin) (1) , quercetin 3- O-β -D-glucopyranoside (Isoquercetrin) (2) , Quercetin (3) , Catechin (4) , quercetin 3- O-α- L-rhamnospyranoside (Quercetrin) (5) . The AME of P. racemosa significantly alleviated the UC by decreasing the disease activity index and Wallace score. Additionally, GSH, CAT, and SOD were increased, and MDA was decreased, suggesting AME’s antioxidant activity. The decreased levels of WBCs, neutrophils, TNF-α, IL-1β, IL-6, MPO, and NF-κB p65 support the AME’s anti-inflammatory properties. The highest activity was recorded for the dose of 1000 mg/kg. These findings were in harmony with the histopathological examination and the Alcian Blue staining for mucin content. The current study revealed that the AME of P. racemosa has protective activities against UC in rats via its antioxidant and anti-inflammatory properties may be attributed to its phenolic profile.

Chemical composition and biological activities of nine essential oils obtained from Algerian plants - Chaima Guendouz; Hadjira Guenane; Boulanouar Bakchiche; Roberta Ascrizzi; Guido Flamini; Sanaa K. Bardaweel; Ahmed M. Sayed; Mosad A. Ghareeb (Natural Product Research, 2026)

Mechanistic insights into trimetazidine's protection against bladder ischemia-reperfusion injury via mirR-211/CHOP modulation and SIRT1/AMPK/PGC1α-mediated mitochondrial biogenesis - Sultan Alrashdi; Shimaa K. Mohamed; Mohamad Elbaz; Elsayed K. El-Sayed (Toxicology and Applied Pharmacology, 2026)

Corn residue alters phosphorus sorption and retention dynamics in a leaching-prone soil - Ziwei Li; Mariam K. Sorour; Zhiming Qi; Eman El Sayed; Shiv O. Prasher (Soil and Tillage Research, 2026)

Adapting rodent cued threat conditioning to planarians: Memory acquisition, consolidation, and reconsolidation - Fionnghuala L.J. James; Sayed K. Ahamed; Cheng Yang; Jigme Thinley; Carmelo M. Vicario; Juan J. Canales; Sukhwinder S. Sohal; Richard Wilson; Luke R. Johnson; Vanni Caruso (Behavioural Processes, 2026)

Geological characteristics and economic potential of paleozoic formations in the Um Bogma Area, Southwestern Sinai, Egypt - Fatma Ramadan; Sami K. Aita; Abd Elazeam Sayed; Ahmed G. Hassan; Abdulgafar K. Amuda; Mohamed Faisal (Euro-Mediterranean Journal for Environmental Integration, 2026)

New insights into the potential effects of date palm seed powder supplementation on the growth, hemato-biochemical indices, organ histology, and gene expression in Rahmani sheep - Hesham S. Ghazzawy; Nashi K. Alqahtani; Roshmon Thomas Mathew; Hassan M. Ali-Dinar; Osama H. Mahmoud Hassan; Hebatallah M. Saad; Yasmin M. Abd El-Aziz; Ehab El-Haroun; Moaheda E.H. Eissa; El-Sayed Hemdan Eissa (Tropical Animal Health and Production, 2026)

Integration of Metabolic Pathways and Micronutrient Signals Influences Neurodevelopment by Modulating Neural Stem Cell Dynamics - Sayed Chandini; Debangana Dey; Tina Gulati; Amit Mishra; Yogita K. Adlakha (Molecular Neurobiology, 2026)

Dapagliflozin ameliorates cisplatin-induced cognitive impairments in rats: Cross-talk between miRNA-21/p-ERK/p-38 MAPK and wnt/β-catenin signaling pathways - Abeer M. Shaheen; Rabab H. Sayed; Gouda K. Helal; Mohammed F. El-Yamany; Mohamed I. Fahmy (NeuroToxicology, 2025)

Guar gum-based systems formulated with encapsulated propolis extract for minimally processed fruits and confectionery packaging - Rowaida K. Khalil; Nadeen B. El-Sayed; Rawan H. El-sayed; Rahma M. Sallam; Asmaa Y. Abdelnabi; Nouran S. Soliman; Rawan A. Ibrahim; Menna-tallah A. Ibrahim; Muhammed R. Sharaby; Dalia S. Abdelrahim (Food Hydrocolloids, 2025)

Triazole-functionalized compounds as promising antifungal agents: Synthesis, biological evaluation, and mechanistic insights - Basmah Almohaywi; Hany E. A. Ahmed; Ahmed Kotb; Abdullah Ashraf; Moaz Alsedawy; EL-Sayed E. Habib; Ahmed K. B. Aljohani; Khalid A. Alosaimi; Aryam S. Alharbi; Samar F. Miski; Mohamed M. Elsebaei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

MALAT1 SNP (rs619586) shows a protective effect against type 1 diabetes mellitus, while the miR-146a SNP (rs57095329) is linked to an increased risk of developing the disease - Soha M. Hamdy; Heba A. Ibrahim; Omayma O. Abdelaleem; Olfat G. Shaker; Sherin K. Hussein; Sara M. A. K. Massoud; Ola N. Sayed (Molecular Biology Reports, 2025)

Sustainable integrated oil-palm livestock practice to enhance soil organic matter and carbon sequestration potential - Y. Umar; K. Sayed; M. I. Syakir; T. K. Al-Saedi; B. Azhar; K. A. Tohiran; F. Nobilly (International Journal of Environmental Science and Technology, 2025)

Potential symbiotic effects of date palm seed extract on growth, immunity, antioxidant activities, gut microbiota, expression levels, and Vibrio parahaemolyticus resistance in Shrimp - Roshmon Thomas Mathew; Nashi K. Alqahtani; Hesham S. Ghazzawy; Ehab El-Haroun; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Nagarajan Ganesan; Amel M. El Asely; Layla A. Almutairi; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; El-Sayed Hemdan Eissa (Frontiers in Marine Science, 2025)
Date Palm Seed Extract (DPSE) is known to possess beneficial health-promoting and growth-boosting properties, but its specific influence on whiteleg shrimp ( Litopenaeus vannamei) health and physiology has yet to be fully explored. Hence, this study examined how dietary DPSE inclusion impacted growth performance, antioxidant status, immune response, hepatic tissue health, inflammation-related gene expression, and resistance to Vibrio parahaemolyticus in shrimp. The study involved four experimental groups of shrimps that were fed diets with varying DPSE inclusions: 0 (DPSE0), 1 (DPSE1), 2 (DPSE2), and 4 (DPSE4) g/kg diet over a 70-day period. The results indicated that dietary DPSE supplementation led to significantly higher (P<0.05) concentrations of whole-body composition (crude protein, gross energy, and crude lipid) in the treated groups. Conversely, the ash content was significantly reduced (P<0.05) in all DPSE-treated shrimp groups compared to the shrimp fed the control diet. Shrimp-fed DPSE-supplemented diets showed a significantly higher total hemocyte count (THC) compared to the control group (P<0.05). The levels of immunological parameters (phagocytosis, phenoloxidase, and lysozyme) and antioxidant status (superoxide dismutase and catalase) were significantly improved with increasing dietary DPSE levels, indicating a dose-dependent effect (P<0.01). The supplementation of DPSE at 1, 2, and 4 g in shrimp diets significantly improved the mRNA expression of immune-related genes ( LGBP, PX, PPA ) and antioxidant genes ( cytMnSOD , mtMnSOD ) compared to the control group (P<0.001). Both total aerobic bacteria and total enteric bacteria were significantly reduced in all DPSE-supplemented groups (P<0.05) compared to the control diet. Dietary inclusion of DPSE improved hepatopancreas tissues and significantly increased resistance to Vibrio parahaemolyticus in shrimp. The results indicate that the dietary inclusion of DPSE can enhance the growth, disease resistance, and overall health of shrimp by regulating immune function, antioxidant status, and immune associated genes regulation. This highlights its potential for sustainable and environmentally beneficial applications in aquaculture.

Assessment of urban heat island effects in industrial areas of Egypt using robust statistical methods - Islam Hamdi; Elsayed K. AbdAlmapoed; Sayed R. AbdElaal (Remote Sensing Applications: Society and Environment, 2025)

Effects of strand corrosion on flexural behavior of prestressed concrete beams: Experimental and analytical investigations - Mshtaq Ahmed; Ahmed K. El-Sayed; Abdulrahman M. Alhozaimy; Abdulaziz I. Al-Negheimish (Engineering Structures, 2025)

Preparation and optimization of eco-friendly inorganic geopolymer membrane - A. M. El-Sayed; H. Abdallah; M. Abdel-Goad; R. Abobeah; Sh. K. Amin (International Journal of Environmental Science and Technology, 2025)
The most common and widely used technique for water and wastewater treatment is membrane separation. This research was applied to fabricate an eco-friendly, low-cost, and sustainable geopolymer membrane that can be used in water treatment. A geopolymer membrane is fabricated using fired clay brick waste, the effect of several variables on the apparent porosity, compressive strength of the membrane, iron and manganese rejection was studied using response surface methodology, the studied variables are zeolite addition in the range of 0–25% by weight, curing temperature at the range from 50 to 90 °C and curing time ranging from 1 to 3 days. According to experimental results, the optimum membrane is prepared using only fired clay brick waste, cured at 70 °C for 1 day. Long-term performance test and fouling test were performed to ensure membrane durability, thus the flux recovery ratio was 97.94%, while the total fouling ratio was 3.66%, of which 1.6% was reversible. These membranes were further characterized through Fourier transform infrared spectroscopy, scanning electron microscope, and pore size distribution, and the results confirmed that the membrane had micropores with an average pore diameter of 0.1212 µm. The optimum membrane was used in a real water application and the manganese and iron rejection reached 99.8% and 90% respectively.

Dietary pterostilbene for improving the whiteleg shrimp (Litopenaeus vannamei): In vivo and in silico insights into growth, hemolymph physiology, redox state, immune function and resistance to Vibrio parahaemolyticus - Roshmon Thomas Mathew; Nashi K. Alqahtani; Hesham S. Ghazzawy; Layla A. Almutairi; Mohammed A. Alqahtani; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Nagarajan Ganesan; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Zulhisyam Abdul Kari; Fatma Mahsoub (Aquaculture International, 2025)

The microbiota-gut-brain-axis theory: role of gut microbiota modulators (GMMs) in gastrointestinal, neurological, and mental health disorders - Al-Hassan Soliman Wadan; Mostafa K. Abd El-Aziz; Doha El-Sayed Ellakwa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
The modulation of gut microbiota presents promising therapeutic possibilities for various health conditions, ranging from gastrointestinal infections to neurodegenerative and mental health disorders. Among the available interventions, gut microbiota modulators (GMMs) such as probiotics and prebiotics have demonstrated significant potential in infection prevention and neuroprotection. Despite these encouraging findings, the clinical application of GMMs remains challenging due to safety concerns and inconsistent effectiveness across diverse patient populations. These factors create substantial barriers to the widespread adoption of microbiota-based therapies in clinical practice. To overcome these challenges and fully leverage the therapeutic potential of microbiota modulation, this review explores the feasibility of repurposing GMMs for managing multiple health disorders. A broad spectrum of microbiota-targeted strategies is examined, including dietary modifications, fecal microbiota transplantation, bacteriophage therapy, microbiome engineering, and immune system modulation. A particularly innovative approach involves integrating GMMs with pharmaceutical delivery systems to enhance therapeutic efficacy while mitigating potential adverse effects. This integrative strategy underscores the pivotal role of the gut microbiome in health and disease, supporting the development of precision medicine tailored to individual patient needs. By combining GMMs with targeted delivery mechanisms, this approach not only improves treatment effectiveness but also addresses critical concerns regarding safety and patient variability. Furthermore, this review outlines future research directions within the rapidly evolving field of microbiota modulation, emphasizing the necessity of comprehensive clinical trials and long-term safety evaluations. By critically assessing both the challenges and opportunities associated with microbiota-based interventions, this study provides a strategic framework for translating experimental research into viable clinical applications. A holistic approach to gut microbiota modulation has the potential to redefine treatment paradigms, offering personalized therapeutic strategies for a wide range of disorders and advancing the broader field of precision medicine.

Adsorption of light green dye using Mg–Al-layered double hydroxides (LDHs) with carbonate and nitrate anions - S. F. Al-Furhud; R. M. K. Mohamed; I. Alsohaimi; M. M. Kamel; M. Y. El-sayed; H. M. Youssef; A. M. Aldawsari; H. M. A. Hassan (International Journal of Environmental Science and Technology, 2025)

Evaluation of spawning induction, egg incubation, and larval rearing of sea bass (Dicentrarchus labrax) in groundwater and seawater resources through different water management systems - Reham M. K. Negm; Heba Saad El-Sayed; Hadir A. Aly (Aquaculture International, 2025)
This study evaluated the viability of using groundwater (GW) compared to seawater (SW) in European sea bass ( Dicentrarchus labrax ) aquaculture. Wild broodstock were captured 2 months before spawning and acclimated to tanks with either SW or GW 1 week prior. Females received HCG injections in both water types. Fertilized eggs were collected into six conical tanks supplied with SW or GW. At 7 days post-hatch (dph), larvae were transferred to 12 rearing tanks with SW or GW, using either flow-through or static water systems (three replicates per treatment). Growth performance and survival were monitored up to 60 dph. The results revealed that spawning induction of European sea bass broodstock failed in GW while succeeded with egg fertilization and hatchability up to 97 ± 1% in SW. Hatching was 96 ± 1% for the fertilized eggs transferred from SW to GW incubators. However, the newly hatched larvae suffered high mortality up to 7 dph, which gradually decreased with the start of exogenous feeding. During the period from 7 to 60 dph, larvae and post-larvae showed normal viability and survival with either flow-through or static water systems in SW and GW. At the end of the experiment, the results indicated that water sources in combination with the water-rearing systems significantly affected post-larvae performance. Larval survival was significantly higher in both GW systems (static: 88.8 ± 2.1%, flow-through: 89.9 ± 5.6%) and in the static SW system (84.15 ± 2.8%) compared to the flow-through SW system (70.4 ± 5.8%). Moreover, the final length of larvae at 60 dph was significantly higher in the static GW system (2.27 ± 0.09 cm). In addition, larvae reared in static GW had higher final weight (140. 00 ± 4.24 mg). Total protein and total lipid contents were significantly higher in larvae reared in GW than those reared in SW for both water systems. The study suggested a static GW system for European sea bass larval rearing starting from 7th dph onwards to achieve better larval quality and higher survival. Future research is needed to enhance GW with new technologies to accommodate D. labrax– induced spawning and newly hatched larval rearing.

Protective potential of bempedoic acid as an AMPK activator in tamoxifen-induced steatohepatitis in rats - Mona Mosaad; Elsayed K. El-Sayed; Engy M. El Morsy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Despite the beneficial therapeutic effects of tamoxifen (TAMX) against breast cancer, long-term treatment with TAMX enhances the development of metabolic dysfunction-associated steatotic liver disease (MASLD), including steatohepatitis. Bempedoic acid (BA) is a recently approved lipid-lowering drug for dyslipidemia. Our study aimed to examine the potential impact of BA against TAMX-induced steatohepatitis in rats and underline the possible molecular pathways involved. Twenty-four adult female rats were allocated into 4 groups ( n = 6): Control, TAMX (45 mg/kg), BA (15 mg/kg), and BA (30 mg/kg) groups. BA was given orally by gavage for 15 consecutive days. TAMX was administered to all rats except the normal control rats. Co - treatment of BA with TAMX showed well-organized structures of the hepatocytes in the histopathological sections. BA significantly improved liver function and lipid profile, demonstrating dose-dependent hepatoprotective effects. Mechanistically, BA significantly decreased oxidative stress by decreasing the level of malondialdehyde (MDA) and increasing the level of superoxide dismutase (SOD), significantly reduced inflammatory cytokines such as nuclear factor-kappa B (NF-κB/p65) and tumor necrosis factor-alpha (TNF-α), significantly inhibited lipogenesis by decreasing sterol regulatory element binding protein 1c (SREBP-1c), fatty acid synthetase (FAS), acetyl-coenzyme A carboxylases (ACC), ATP-citrate lyase (ACL), and significantly promoted fatty acid oxidation be enhancing carnitine palmitoyl transferase 1 significantly (CPT-1) through AMP-activated protein kinase (AMPK) activation. These findings suggest BA as a potential adjunct therapy for TAMX-induced metabolic dysfunction-associated steatohepatitis (MASH).

Remote sensing, petrogenesis and tectono-magmatic evolution of the Wadi Queh-Wadi Abu Shigeili area: a window into the transitional history of the central Egyptian-Nubian Shield from pre-plate collision to post-collision magmatism - Osama K. Dessouky; El-Sayed H. El-Sawey; Yasser S. Badr; Sobhi Nasir; Gehad M. Saleh; Ahmed M. Dardier; Kamal A. Ali; Abdel-Rahman Fowler; Saleh E. Ammar; Ahmed M. Ismail; Mahmoud M. Hassan (International Journal of Earth Sciences, 2025)

Whole genome sequencing identifies monogenic disease in 56.1% of families with early-onset steroid-resistant nephrotic syndrome - Neveen A. Soliman; Mohamed A. Elmonem; Ahmed F. El-Sayed; Eman Ramadan; Ahmed M. Badr; Fatma M. Atia; Rasha Helmy; May O. Amer; Ahmed Abd El-Raouf; Fadya M. El-Garhy; Omnia M. Abdel-Haseb; Tokka M. Hassan; et al. (Human Genetics, 2025)
Genetic causes of steroid-resistant-nephrotic-syndrome (SRNS) represent a rapidly growing number of monogenic diseases. The reported diagnostic yield of various studies applying genetic panels and exome-sequencing to diagnose SRNS is usually < 30%. We performed genome-sequencing in a cohort of Egyptian SRNS patients. We recruited 47 SRNS patients belonging to 41 unrelated families [28 males/19 females; median (range): 6 (0.5–22 years)]. We established a pipeline for genome sequencing, bioinformatics analysis, variant curation and protein modeling at the Egypt Center for Research and Regenerative Medicine (ECRRM). Disease-causing variants were detected in 27/47 patients (57.4%) belonging to 23/41 families (56.1%), including nine novel variants in NPHS1, NPHS2, COL4A3, MYO1E, NUP93, PLCE1, PODXL, SMARCAL1 and WT1 . Novel variants were confirmed by Sanger sequencing and were segregated in families of affected patients. NPHS2 was the most common causative gene in 8/23 (34.8%) of confirmed families, followed by NPHS1 , WT1 , and SMARCAL1 in 2/23 families (8.7%) each. All detected missense variants were evaluated through protein modeling and were predicted deleterious. Our study expanded the spectrum of SRNS disease-causing variants and revealed a monogenic cause in 56.1% of investigated families. In our cohort, no deep intronic or regulatory variants were detected by genome-sequencing. Pursuing genetic diagnosis in SRNS patients is crucial to inform clinical decision making, genetic counseling, transplantation strategy and prenatal diagnosis thus improving clinical outcome of affected patients.

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

BDCN_UNet: Advanced shoreline extraction techniques integrating deep learning - Amira S. Mahmoud; Sayed A. Mohamed; Ashraf K. Helmy; Ayman H. Nasr (Earth Science Informatics, 2025)
The delineation of shorelines, marking the dynamic boundary between land and sea, is crucial for coastal management and ecological conservation. This research investigates various methods for automatic shoreline extraction from satellite images, utilizing cost-effective and regularly available remote sensing data. A deep learning framework is used for the comparison that combines semantic segmentation (UNEt) and edge detection (Bi-Directional Cascade Network, or BDCN) to make the results more accurate. The study focuses on the northern coast of Egypt, a region with diverse landscapes and significant human interventions. We’ve made progress in our methods by using advanced image processing, the CoastSat Toolkit, the BDCN_UNet framework, time series analysis, and deep learning networks to look at and keep an eye on Egypt’s North Coast’s future plans in more detail. This study captures the intricate interplay between natural and human factors in coastal environments, offering valuable insights for sustainable coastal development. The performance analysis of four models (UNet, Pyramid Scene Parsing Network, DeepLabV3, and BDCN_UNet) applied to three satellite datasets (Sentinel-2, PlanetScope, and Pleiades) showed that PlanetScope and Pleiades consistently yield higher accuracy (0.90–0.99), while Sentinel-2 proved more challenging, particularly for Pyramid Scene Parsing Network and DeepLabV3. UNet and BDCN_UNet exhibited robust performance across all datasets, especially with Pleiades delivering the best results overall.

Red Sea warming and its links to the Red Sea dipole and upwelling mechanisms - Ahmed M. El Kenawy; Mohammad Hadi Bordbar; Emad K. Mohamed; Mohamed M. Abdelaal; Beatriz Fernandez-Duque; Matthew F. McCabe; Mohamed El Alfy; Azza Ragab; Hosam Ismael; Shimaa Mebed; Sayed M. Robaa; Hassan Aboelkhair (Journal of Marine Systems, 2025)

Neuroprotective activities of coixol: in vitro and in silico studies - Yhiya Amen; Ahmed Othman; Ahmed M. Sayed; Ashraf K. El-Damasy; Amira Mira (Natural Product Research, 2025)

Decorin alleviates non-alcoholic fatty liver disease in rats with polycystic ovary syndrome - Hany A. Elkattawy; Amira Ebrahim Alsemeh; Lashin Saad Ali; Mona Mostafa Ahmed; Asmaa Monir Eltaweel; Farha M. Shaikh; Ahmed Behiry; Ahmed El-Sayed Hassan; Deema Kamal Sabir; Dalia Mahmoud Abdelmonem Elsherbini; Sahar K. Ali; Madaniah Omar Zakari; et al. (Tissue and Cell, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

E-cigarettes increase the risk of adenoma formation in murine colorectal cancer model - Ibrahim M. Sayed; Anirban Chakraborty; Kaili Inouye; Leanne Dugan; Stefania Tocci; Ira Advani; Kenneth Park; Samvel Gaboyan; Nikita Kasaraneni; Benjamin Ma; Tapas K. Hazra; Soumita Das; et al. (Archives of Toxicology, 2025)

The pyrolytic distillation of waste lubricants with waste oilfield scale into value-added fuel - Sayed K. Attia; Ahmed M. Rashad; Mohamed Mohamady Ghobashy; Asmaa. E. Elsayed; Doaa I. Osman (Fuel, 2024)

Understanding the nature of blast resistance in combined bacterial leaf blight and blast gene pyramided lines of rice variety tellahamsa - E. Ramprasad; Ch V Durga Rani; C. N. Neeraja; G. Padmavathi; R. Jagadeeshwar; C. Anjali; Priya Thakur; K. N. Yamini; G. S. Laha; M. Srinivas Prasad; Seham Sater Alhelaify; Ohud Muslat Aharthy; et al. (Molecular Biology Reports, 2024)

Retraction Note: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s Disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2024)

Biosynthesis of Silver, Copper, and Their Bi-metallic Combination of Nanocomposites by Staphylococcus aureus: Their Antimicrobial, Anticancer Activity, and Cytotoxicity Effect - Mohsen A. Sayed; Tahany M. A. Abd El-Rahman; H. K. Abdelsalam; Sayed M. S. Abo El-Souad; Rawan Muhammad Shady; Radwa Abdallnasser Amen; Mostafa Ahmed Zaki; Martina Mohsen; Sara Desouky; Samar Saeed; Seif Omar; Asmaa A. H. El-Bassuony (Indian Journal of Microbiology, 2024)
The present study outlines an easy, cheap, and environmentally friendly way to make Staphylococcus aureus -mediated bimetallic silver-copper nanocomposites (Ag/Cu) that can fight cancer and germs. The gram-positive S. aureus synthesized Ag, Cu, and their bi-metallic nanocomposites extracellularly. We aimed to prepare the bimetallic nanocomposite in two different ways, and we compared them in terms of characterization and biological applications. The first one is a bimetallic nanocomposite (Ag/Cu b ) that was made by mixing Ag and Cu metal ions in equal amounts (50:50). Then, the whole mixture was reduced. The second is the after-reduction bimetallic nanocomposite (Ag/Cu a ), in which each metal ion was reduced separately, and then the nanocomposites were mixed (50:50%) during biological applications. Nanocomposites were characterized using UV–visible spectrophotometry, Fourier-transform infrared spectroscopy, dynamic light scattering, and transmission electron microscopy. The results demonstrated that surface plasmon bands were at 320 nm for Ag NPs and 525 nm for Cu NPs, and a shift from these peaks was observed at 290 nm in the Ag/Cu b bimetallic nanocomposite. The synthesized nanocomposites were confirmed to be in the nanoscale with 20, 40, and 80 nm spherical crystals, respectively. Nanocomposites were assayed for their antimicrobial activity against the gram-negative Pseudomonas aeruginosa , the acid-fast Mycobacterium smegmatis , the gram-positive Bacillus cereus, and S. aureus, in addition to three fungal species, which were Aspergillus flavus , A. fumigatus, and Candida albicans . The minimum inhibitory concentration and minimum bactericidal concentration were determined. The Ag/Cua/Cuaetallic nanocomposite was the most potent antimicrobial compound. The anticancer activity of the tested compounds was assayed against the hepatocellular carcinoma cell line (HepG-2). Low cytotoxic activity was recorded in most assayed nanocomposites against the baby hamster kidney cell line (BHK).

Phytochemical profiling of Ananas comosus fruit via UPLC-MS and its anti-inflammatory and anti-arthritic activities: In Silico, In Vitro and In Vivo Approach - Sally E. Khaled; Faten Mohamed Ibrahim; Eman Abdelsalam; Kawkab A. Ahmed; Asmaa K. Al-Mokaddem; Wedian El Sayed Ashour; Amany A. Sleem; Reda Sayed Mohammed (Biocatalysis and Agricultural Biotechnology, 2024)

The Egyptian Nile estuarine habitats: a review - Khaled M. Abdelsalam; Hermine R. Z. Tadros; Abeer A. Moneer; Mona Kh. Khalil; Samia K. Hamdona; Laila Shakweer; Madelyn N. Moawad; Abeer A. M. El-Sayed; Ghada F. El-Said; Mona M. Ismail; Aida H. Shobier; Shimaa Hosny; et al. (Aquatic Sciences, 2024)
Estuaries are nutrient-rich environments characterized by a gradient in salinity due to the mixing of freshwater and seawater. These bodies of water play vital functions in nature and provide a wide variety of essential ecosystem services. In general, many natural and/or man-made activities have strongly stressed the Egyptian Nile estuarine habitats, as has the water shortage that was expected after the construction of the Grand Ethiopian Renaissance Dam. In recent decades, the Nile Delta has been considered to be one of the most important productive oil-producing petroleum regions due to onshore and offshore gas discoveries alongside gasoline and base oil generation. Up-to-date systematic reviews of the Egyptian estuarine habitats (Rosetta and Damietta) are missing, and the review reported here was undertaken to fill this gap. In this review, we consider the physical, chemical, geological, pollution, and biological parameters of Egyptian Nile estuaries. In this context, our aim is to contribute to a broader understanding of the Egyptian estuarine habitat; moreover, we provide potential warning signals that may aid in estuarine environmental protection. We found that most of the previous studies had focused on the two branches of the Nile or on the marine waters adjacent to these branches, and that only a few studies focused on the estuarine habitats themselves. In most of these previous studies, the salinity gradient of water was reported to be a significant factor in the distribution of the different measured parameters while, in contrast, more recent investigations confirm the importance of potential effluent sources in affecting the distribution of these parameters. We highly recommend that the data reported here be updated in future studies on different environmental aspects.

Silver nanoparticles incorporated with superior silica nanoparticles-based rice straw to maximize biogas production from anaerobic digestion of landfill leachate - Mona T. Al-Shemy; Filip Gamoń; Aly Al-Sayed; Mohamed S. Hellal; Aleksandra Ziembińska-Buczyńska; Gamal K. Hassan (Journal of Environmental Management, 2024)

Enhanced upregulation of SIRT1 via pioglitazone and ligustrazine confers protection against ethanol-induced gastric ulcer in rats - Sara A. Mahmoud; Abeer Elkhoely; Elsayed K. El-Sayed; Amany A. E. Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Gastric ulcer is a disturbing disease that impacts many people worldwide. Pioglitazone (Piog), a thiazolidinedione, and ligustrazine (Ligu), a natural component of Ligusticum chuanxiong possess gastroprotective properties. However, the underlying mechanism is not well elucidated. The present study aimed to investigate the gastroprotective effects of Piog (15 mg/kg, p.o.), Ligu (15 mg/kg, p.o.), and their combination against ethanol-induced gastric ulcer in rats. Omeprazole (10 mg/kg) was used as a standard. Pre-treatment for 7 days with Piog, Ligu, and (Piog+Ligu) effectively alleviated ethanol-predisposed oxidative stress and inflammation through restoring HO-1, GSH, and SOD tissue levels and decreasing elevated MDA, TNF-α, ICAM, I-NOS, and IL-1β contents. Moreover, Piog, Ligu, and (Piog+Ligu) markedly inhibited the ethanol-induced increase of gastric NF-KB and BAX. In contrast, this pre-treatment regimen significantly accelerated protein expression of SIRT1, Nrf2, and Bcl-2, along with autophagic proteins, ATG5 and Beclin. Interestingly, macroscopic, histopathological examination and mucin content were in harmony with previous results, where pre-treatment with Piog, Ligu, and (Piog+Ligu) showed a declined mucosal injury as evidenced by the remarkable decrease of the ulcer area percentage by 62.3%, 38.7%, and 91.2%, respectively, compared to the ethanol-ulcerated group. In conclusion, Piog and Ligu exhibited remarkable gastroprotective properties. Our study was the first to show that Piog, Ligu, and (Piog+Ligu) ameliorated oxidative stress, inflammation, and apoptosis and accelerated the autophagic process via the upregulation of the upstream SIRT1 protein. It is worth mentioning that future studies are needed to pave the way for the clinical use of Piog and Ligu as gastro-protective agents.

Exploring the dynamical bifurcation and stability analysis of Nipah virus; novel perspectives utilizing fractional calculus - Sehrish Ramzan; Saima Rashid; Muzamil Abbas Shah; Sayed K. Elagan (Modeling Earth Systems and Environment, 2024)

From Proliferation to Protection: Immunohistochemical Profiling of Cardiomyocytes and Immune Cells in Molly Fish Hearts - Giacomo Zaccone; Doaa M. Mokhtar; Alessio Alesci; Gioele Capillo; Marco Albano; Manal T. Hussein; Marialuisa Aragona; Antonino Germanà; Eugenia R. Lauriano; Ramy K. A. Sayed (Fishes, 2024)
Unlike adult mammalian cardiomyocytes, cardiomyocytes in teleosts display high proliferative capacity throughout adulthood. This study aimed to identify the immunohistochemical profiles of cardiomyocytes and immune cells in the hearts of Molly fish by assessing the immunolabelling expression of key proteins involved in cell proliferation, differentiation, and tissue protection. The cardiac anatomy of Molly fish includes the atrium, ventricle, and bulbus arteriosus. The expression of SOX9, NF-κB, myostatin, and S100 proteins in myocardial cells indicates the proliferative features of the heart in Molly fish. The bulbus arteriosus is characterized by collagenous chambers and smooth muscle cells that express Ach and iba1. The atrium of Molly fish serves as a storage unit for rodlet cells and immune cells. Rodlet cells displayed immunoreactivity to NF-κB, iba1, Olig2, Ach, and S100 proteins, suggesting their roles in the immune response within the heart. Furthermore, telocytes (TCs) have emerged as a significant component of the atrium of Molly fish, expressing Ach, CD68, S100 protein, and iba1. These expressions indicate the involvement of TCs in multiple signaling pathways that contribute to heart architecture. This study delineates the intricate relationship between cardiomyocytes and innate immune cells in Molly fish.

Soleus H-reflex amplitude modulation during walking remains physiological during transspinal stimulation in humans - Abdullah M. Sayed Ahmad; Meghan Raphael; Jessy Feng Han; Yoseph Ahmed; Mohamed Moustafa; Shammah K. Solomon; Andreas Skiadopoulos; Maria Knikou (Experimental Brain Research, 2024)

Nano-selenium impacts on growth performance, digestive enzymes, antioxidant, immune resistance and histopathological scores of Nile tilapia, Oreochromis niloticus against Aspergillus flavus infection - El-Sayed Hemdan Eissa; Walaa K. Bazina; Yasmin M. Abd El-Aziz; Nadia A. Abd Elghany; Wesam A. Tawfik; Monga I. Mossa; Ola Hasan Abd El Megeed; Nadia N. B. Abd El-Hamed; Adel F. El-Saeed; Ehab El-Haroun; Simon J. Davies; Oliver J. Hasimuna; et al. (Aquaculture International, 2024)
The present study examined the impacts of varying amounts of selenium nanoparticles (Se-NPs) as a natural antioxidant and metabolic regulator on growth performance, antioxidant capacity, digestive enzymes and immune resistance of Oreochromis niloticus challenged to Aspergillus flavus infection. For 60 days, fish were fed the experimental diet of 30% crude protein up to apparent satiation three times a day. Se-NPs were added to the control diet at different levels of 0.0 (control), 0.5 (T1), 1.0 (T2) and 1.5 (T3) mg/kg diet to fed monosex Nile tilapia fingerlings with average initial weight (4.5 ± 0.5 g). Fish were randomly distributed in 12 tanks 100 L at a density of 20 fish per tank after 2-week acclimation to represent four treatments in triplicates. The results indicated that the growth indices, feed efficiency and survival rate were significantly enhanced ( P P Aspergillus flavus , a decreasing mortality rate was observed, which clearly shows that selenium nanoparticles boosted the fish’s immune response at T2. The intestinal morphology as villus length, villus width, muscular fibres layer thickness and absorption intestinal zone after challenged with A. flavus infection were considerably enhanced ( P P

Recent advances in graphene-based nano-membranes for desalination - Imran Ali; Sayed Zenab Hasan; Hermenegildo Garcia; Michael K. Danquah; Gunel Imanova (Chemical Engineering Journal, 2024)

Echinacea purpurea extract intervention for counteracting neurochemical and behavioral changes induced by bifenthrin - Khaled G. Abdel-Wahhab; Rehab S. Sayed; Doaa G. EL-Sahra; Laila K. Hassan; Ghada M. Elqattan; Fathia A. Mannaa (Metabolic Brain Disease, 2023)
This study was conducted to elucidate the possible protective efficiency of Echinacea purpurea hydroethanolic extract (EchEE) against bifenthrin (BIF)-induced neuro-chemical and behavioral changes in rats. Total phenolics content, reducing power and radical scavenging activity of EchEE were estimated. Four groups of adult male albino rats were used (10 rats each) as follows: 1) Control healthy rats ingested with placebo, 2) Healthy rats orally received EchEE (465 mg/kg/day), 3) Rats intoxicated with BIF (7mg/kg/day) dissolved in olive oil, and 4) Rats co-treated with EchEE (465 mg/kg/day) besides to BIF (7mg/kg/day) intoxication. After 30 days, some neuro-chemical and behavioral tests were assessed. The behavioral tests revealed that rats received BIF exhibited exploratory behavior and spatial learning impairments, memory and locomotion dysfunction, and enhanced anxiety level. Biochemical findings revealed that BIF induced-oxidative stress in the cortex and hippocampus; this was appeared from the significant rise in malondialdehyde (MDA) and nitric oxide (NO) levels, coupled with decreased catalase (CAT), superoxide dismutase (SOD), paraoxonase-1 (PON-1) activities, and reduced glutathione (GSH) level in both brain areas. Also, BIF induced a significant increase caspas-3, tumor necrosis factor alpha (TNF), and interleukin-1beta (IL-1ß) in both areas; dopamine and serotonin levels, and ACh-ase activity were markedly decreased in both areas. Interestingly, treatment of rats with EchEE in combination with BIF resulted in a significant decrease in oxidative stress damage, and modulation of the apoptotic and pro-inflammatory markers. Also, EchEE markedly improved behavioral activities and neurotransmitters level that were impaired by BIF. In conclusion, the present study clearly indicated that EchEE can attenuate brain dysfunction induced by pesticides exposure through preventing the oxidative stress. This may be attributed to its high antioxidant component.

Immune Cell Profiling in the Ovarian Stroma of a Viviparous Fish during the Breeding Season: A Histological and Immunohistochemical Investigation - Ramy K. A. Sayed; Doaa M. Mokhtar; Madeha Ahmed Hashim; Ahmed S. Aly; Giacomo Zaccone; Marco Albano; Alessio Alesci; Nada Abdellah (Fishes, 2023)
The molly fish is a member of viviparous teleosts that are characterized by the fusion of the right and left ovaries during their early embryonic development. This fusion results in a singular and saccular ovary, where the germinal epithelium lines the internal lumen. The present study aimed to identify the immune cells in the ovarian stroma of Molly fish during the breeding season using histological and immunohistochemical analysis. Histological examination of the ovaries displayed oocytes at all different stages of development and degeneration. The ovocoel, a lymph-filled space, remains in the center of the ovary and branches posteriorly, creating the lumen of the gonoduct. The ovarian wall is composed of three layers: the mesothelium, tunica albuginea, and germinal epithelium. The developing ova were held together by the stroma, which consisted of vascular collagenous connective tissue clustered with immune cells. Immunohistochemical analysis revealed the presence of clusters of macrophages expressing APG5, IL-1β, TGF-β, S100, NF-κB, CD68, Iba-1, and Ach. Monocytes demonstrated positive immunoreactivity for both APG5 and IL-1β, whereas dendritic cells expressed only APG5. Furthermore, rodlet cells exhibited immunoreactivity for S100 protein, IL-1β, NF-κB, CD68, Nrf2, Ach, myostatin, SOX9, and Iba-1. In contrast, stem cells displayed immunoreactivity for Nrf2, myostatin, and SOX9. In conclusion, the ovarian stroma of Molly fish demonstrated a notable presence of immune cells, indicating their active involvement in immune reactions.

A hybrid deep learning model for rainfall in the wetlands of southern Iraq - Fehaid Alqahtani; Mostafa Abotaleb; Alhumaima Ali Subhi; El-Sayed M. El-Kenawy; Abdelaziz A. Abdelhamid; Khder Alakkari; Amr Badr; H. K. Al-Mahdawi; Abdelhameed Ibrahim; Ammar Kadi (Modeling Earth Systems and Environment, 2023)

Sponge-like zinc oxide nanoparticles loaded xanthan gum/cationic chitosan cryogel: Synthesis, characterization, microbicidal and adsorption of synthetic dye and heavy metal - Samar A. El-Kholy; Emad K. Radwan; Mehrez E. El-Naggar; Shaimaa T. El-Wakeel; Ibrahim El-Tantawy El Sayed (Journal of Environmental Chemical Engineering, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Oxidative Stress and Immunopathological Alterations of Clarias gariepinus Exposed to Monocyclic Aromatic Hydrocarbons (BTX) - Alaa El-Din H. Sayed; Hamdy A. M. Soliman; Shaimaa K. Idriss; Sary Kh. Abdel-Ghaffar; Asmaa A. A. Hussein (Water, Air, & Soil Pollution, 2023)
This study’s goal was to assess the catfish’s response to exposure to monoaromatic petroleum hydrocarbons (benzene, toluene, and xylene) and its recovery after exposure using oxidative stress, histopathological, and immunological changes as biomarkers. Four groups: one as control and other three exposed to benzene (0.762 ng/L), toluene (26.614 ng/L), and xylene (89.403 ng/L), respectively, for 30 days and then recovery period for 30 days. The levels of the cortisol, lipid peroxidation, and cytokines (IL-1β, IL-6) increased significantly ( p < 0.05) after exposure to benzene and xylene compared to control. Superoxide dismutase (SOD), total antioxidant capacity (TAC), and acetylcholinstease (Ach) decreased significantly ( p < 0.05) in fishes exposed to benzene only compared to control group. While glutathione-S-transferase (GST) did not show any change in different treatment groups compared to control group. The histopathological signs of liver exposed to benzene, toluene, and xylene displayed aggregation of melanomacrophages, congestion of sinusoids, vacuolar degeneration of hepatocytes, necrotic area with inflammatory cell infiltration, and thrombus of central vein. Kidney exposed to benzene, toluene, and xylene showed dilatation of Bowman’s space with atrophy of glomerular tuft, lyses of RBCs with mononuclear cell infiltration, multifocal area of hemopoietic tissue necrosis, organized thrombus with perivascular hemorrhage, focal inflammatory cellular reaction, renal tubular necrosis, and thrombus of blood vessels. Spleen exposed to benzene, toluene, and xylene showed hyperplasia of lymphoid follicles in white pulp in a mild degree. These lesions appeared to a mild degree or disappeared completely after recovery period to BTX except spleen. In conclusion, monocyclic aromatic hydrocarbons (BTX) are hazardous to fish and the toxicity level was as benzene > xylene > toluene even though after recovery period.

Assessment of nest architecture and pollination efficiency of Lasioglossum (Evylaeus) marginatum (Helictidae: Hymenoptera) - Showket A. Dar; Kounser Javeed; Laila A. Al-Shuraym; Samy Sayed; Yendrembam K. Devi; Wajid Hassan; Mohamed Morsi M. Ahmed; Naser A. Alkenani; Ivana Tlak Gajger; James John (Biologia, 2023)

Dietary Effects of Nano Curcumin on Growth Performances, Body Composition, Blood Parameters and Histopathological Alternation in Red Tilapia (Oreochromis sp.) Challenged with Aspergillus flavus - El-Sayed Hemdan Eissa; Bothaina A. Alaidaroos; Samyah D. Jastaniah; Mohammad Bodrul Munir; Manal E. Shafi; Yasmin M. Abd El-Aziz; Walaa K. Bazina; Saadiah binti Ibrahim; Moaheda E. H. Eissa; Marina Paolucci; Fatima S. Alaryani; Nadia N. B. Abd El-Hamed; et al. (Fishes, 2023)
This research examined the role of nano curcumin (NC) on growth performances, body composition, and blood parameters of red tilapia (Oreochromis sp.) challenged with Aspergillus flavus. Fish (5.0 g ± 0.30) were randomly distributed in four equal groups (20 fish per pond in triplicates) and fed various concentrations of NC fortified with 0 (Control), 40 mg/kg (NC1), 50 mg/kg (NC2), and 60 mg/kg diet (NC3) of nano curcumin. After eight weeks of the feeding trial, the fish were challenged with A. flavus for 15 days, and the cumulative mortality was recorded. Fish fed with different concentrations of NC improved significantly (p 0.05) difference between NC2 and NC3 treatments. However, NC3 exhibited higher performances. Fish feed supplemented with NC decreased the mortality rate when challenged with A. flavus. Hence, dietary supplementation of NC enhanced the growth and health status of Oreochromis sp. and protected it from A. flavus infection. This study suggests the optimum inclusion level of NC is a 50–60 mg/kg diet.

Recent updates on thienopyrimidine derivatives as anticancer agents - Menna Tallah M. Sayed; Rasha A. Hassan; Peter A. Halim; Afaf K. El-Ansary (Medicinal Chemistry Research, 2023)
Thienopyrimidine derivatives hold a unique place between fused pyrimidine compounds. They are important and widely represented in medicinal chemistry as they are structural analogs of purines. Thienopyrimidine derivatives have various biological activities. The current review discusses different synthetic methods for the preparation of heterocyclic thienopyrimidine derivatives. It also highlights the most recent research on the anticancer effects of thienopyrimidines through the inhibition of various enzymes and pathways, which was published within the last 9 years. Graphical Abstract

Haemato-biochemical, mutagenic, and histopathological changes in Oreochromis niloticus exposed to BTX - Alaa El-Din H. Sayed; Shaimaa K. Idriss; Sary Kh. Abdel-Ghaffar; Asmaa A. A. Hussein (Environmental Science and Pollution Research, 2023)
The study of the DNA damage response in erythrocytes after exposure to volatile organic compounds (VOCs) can present evidence for its potential effect as genotoxic- biomarkers for environmental pollution. Although VOCs are dangerous pollutants, still little is known about hemotoxic, cytotoxic, and genotoxic effects of such pollutants on fish. We optimized an assay method for apoptosis and DNA damage in erythrocytes of adult tilapia fish after 15 days exposure to benzene (0.762 ng/L), toluene (26.614 ng/L), and xylene (89.403 ng/L). The highest level of apoptosis and DNA damage were recorded in benzene-exposed fish, as was the highest level of histopathological alterations in gills, liver, and kidney. The imbalance of the antioxidants profile explained the stress-case reported in exposed fish. These results suggest that hemotoxic, cytotoxic, genotoxic, and tissue damage were recorded after exposure to BTX in Oreochromis niloticus .

A practical model for moment redistribution in statically indeterminate RC beams - Ashot G. Tamrazyan; Yehia A. K. Sayed (European Journal of Environmental and Civil Engineering, 2023)

Multi-functional of TiO2@Ag core–shell nanostructure to prevent hydrogen sulfide formation during anaerobic digestion of sewage sludge with boosting of bio-CH4 production - Gamal K. Hassan; Walaa H. Mahmoud; Aly Al-sayed; Sameh H. Ismail; Ahmed A. El-Sherif; S.M. Abd El Wahab (Fuel, 2023)

Bacillus Species as Direct-Fed Microbial Antibiotic Alternatives for Monogastric Production - Shifa A. Bahaddad; Meshal H. K. Almalki; Othman A. Alghamdi; Sayed S. Sohrab; Muhammad Yasir; Esam I. Azhar; Hichem Chouayekh (Probiotics and Antimicrobial Proteins, 2023)

Intra-articular injection of rAAV-hFGF-2 ameliorates monosodium iodoacetate-induced osteoarthritis in rats via inhibiting TLR-4 signaling and activating TIMP-1 - Mostafa A. Rabie; Rabab H. Sayed; Jagadeesh K. Venkatesan; Henning Madry; Magali Cucchiarini; Nesrine S. El Sayed (Toxicology and Applied Pharmacology, 2023)

Phytochemical and in silico studies for potential constituents from Centaurium spicatum as candidates against the SARS-CoV-2 main protease and RNA-dependent RNA polymerase - Ahmed E. Allam; Mohamed E. Abouelela; Hamdy K. Assaf; Ahmed M. Sayed; Alaa M. Nafady; Mohamed A. El-Shanawany; Fumihide Takano; Tomihisa Ohta (Natural Product Research, 2022)

Preparation and characterization of N-doped ZnO and N-doped TiO2 beads for photocatalytic degradation of phenol and ammonia - Hagar Mandor; Nevine K. Amin; Ola Abdelwahab; El-Sayed Z. El-Ashtoukhy (Environmental Science and Pollution Research, 2022)
N-doped ZnO beads (NZB) and N-doped TiO 2 beads (NTB) were synthesized via a modified sol–gel technique utilizing chitosan (CS)/polyvinyl alcohol (PVA) hydrogel beads as basic support for photocatalyst. Urea was used as a source of nitrogen in the preparation of N-doped ZnO beads, while ammonium acetate, CH 3 COONH 4 , was used as a nitrogen source in the production of N-doped TiO 2 beads. The characteristics of synthesized beads were identified by scanning electron microscope (SEM), X-ray photoelectron spectroscopy analysis (XPS), X-ray diffraction (XRD), N 2 adsorption–desorption isotherms, BET surface area, Fourier transform infrared (FT-IR) measurements, and diffuse reflectance spectroscopy (DRS) studies. The use of the nitrogen doping method for photocatalyst was performed to adjust the bandgap and electrical properties of ZnO and TiO 2 by establishing acceptor defects. NZB and NTB with the intrinsic donor defect of oxygen vacancy and the nitrogen-to-oxygen acceptor defect could be activated by a less-energy UV consumption for efficient pollutant degradation. The results indicated that the as-synthesized NZB achieved much higher degradation activity than NTB, commercial ZnO, and TiO 2 in the decomposition of a binary mixture composed of ammonia and phenol under UV light irradiation.

Dietary curcumin nanoparticles promoted the performance, antioxidant activity, and humoral immunity, and modulated the hepatic and intestinal histology of Nile tilapia fingerlings - Mohsen Abdel-Tawwab; El-Sayed Hemdan Eissa; Wesam A. Tawfik; Heba E. Abd Elnabi; Saadea Saadony; Walaa K. Bazina; Ragaa A. Ahmed (Fish Physiology and Biochemistry, 2022)
The current study investigated the effects of dietary curcumin nanoparticles (C-NPs) on the performance, hemato-biochemical profile, digestive enzymes activities, antioxidant status, humoral immunity, and liver and intestinal histology of Nile tilapia ( Oreochromis niloticus ). Fish (4.3 ± 0.5 g) were fed with diets enriched with 0.0 (control), 15, 30, 45, and 60 mg C-NPs/kg diet up to apparent satiety thrice a day for 60 days. The growth-stimulating effects of dietary C-NPs were significantly observed in terms of final weight, weight gain %, specific growth rate, and feed intake. Compared with the control group, serum amylase, lipase, and proteases activities of Nile tilapia significantly ( P < 0.05) increased alongside the increase in dietary levels of C-NPs in a dose-dependent manner. The counts of red blood cells and white blood cells as well as hemoglobin and hematocrit levels of Nile tilapia fed with 30–60 mg C-NPs/kg diet were statistically ( P < 0.05) higher than fish in the control group with no significant differences among them ( P > 0.05). Moreover, lymphocytes and monocytes significantly ( P > 0.05) increased; meanwhile neutrophils significantly ( P > 0.05) decreased as C-NPs levels in diets increased. In a similar trend, antioxidant (malondialdehyde, superoxide dismutase, catalase, and glutathione peroxidase) and humoral immunity (lysozyme and total immunoglobulin) biomarkers were significantly higher in C-NPs-fed fish. Liver histology showed improvements in the cell architecture of fish fed with C-NPs containing diets up to 45 mg/kg diet. Compared with the control diet, feeding Nile tilapia with C-NPs diets resulted in a higher villi length/width and absorption area. According to the regression curves, the current study recommends using the dietary C-NP with optimum values of 45–55 mg/kg diet to improve the performance, digestive enzymes, antioxidant activities, and immunity response of Nile tilapia.

Biochemical, molecular and cytological impacts of alpha-lipoic acid and Ginkgo biloba in ameliorating testicular dysfunctions induced by silver nanoparticles in rats - Hossam G. Tohamy; Mohamed A. Lebda; Kadry M. Sadek; Mohamed S. Elfeky; Yasser S. El-Sayed; Dalia H. Samak; Heba S. Hamed; Tarek K. Abouzed (Environmental Science and Pollution Research, 2022)

Biological and molecular characterization of fEg-Eco19, a lytic bacteriophage active against an antibiotic-resistant clinical Escherichia coli isolate - Shimaa Badawy; Zakaria A. M. Baka; Mohamed I. Abou-Dobara; Ahmed K. A. El-Sayed; Mikael Skurnik (Archives of Virology, 2022)
Characterization of bacteriophages facilitates better understanding of their biology, host specificity, genomic diversity, and adaptation to their bacterial hosts. This, in turn, is important for the exploitation of phages for therapeutic purposes, as the use of uncharacterized phages may lead to treatment failure. The present study describes the isolation and characterization of a bacteriophage effective against the important clinical pathogen Escherichia coli , which shows increasing accumulation of antibiotic resistance. Phage fEg-Eco19, which is specific for a clinical E. coli strain, was isolated from an Egyptian sewage sample. Phage fEg-Eco19 formed clear, sharp-edged, round plaques. Electron microscopy showed that the isolated phage is tailed and therefore belongs to the order Caudovirales , and morphologically, it resembles siphoviruses. The diameter of the icosahedral head of fEg-Eco19 is 68 ± 2 nm, and the non-contractile tail length and diameter are 118 ± 0.2 and 13 ± 0.6 nm, respectively. The host range of the phage was found to be narrow, as it infected only two out of 137 clinical E. coli strains tested. The phage genome is 45,805 bp in length with a GC content of 50.3% and contains 76 predicted genes. Comparison of predicted and experimental restriction digestion patterns allowed rough mapping of the physical ends of the phage genome, which was confirmed using the PhageTerm tool. Annotation of the predicted genes revealed gene products belonging to several functional groups, including regulatory proteins, DNA packaging and phage structural proteins, host lysis proteins, and proteins involved in DNA/RNA metabolism and replication.

“Anosmia” the mysterious collateral damage of COVID-19 - Abdulrahman K. Ahmed; Reem Sayad; Islam A. Mahmoud; Aya M. Abd EL-Monem; Salma H. Badry; Islam H. Ibrahim; Mahmoud HR Hafez; Mohamed A. El-Mokhtar; Ibrahim M. Sayed (Journal of NeuroVirology, 2022)

Thermal treatment of Kalabsha kaolin deposits, south of the Western Desert, Egypt: contribution to geopolymer production as green building materials - Mohamed W. Abd El-Moghny; Hatem M. El-Desoky; Abdeen M. El-Nagar; Nabil A. Abd El-Hafez; Hossam K. Sharaka; Sayed A. Abouellaban (Arabian Journal of Geosciences, 2022)
Kaolin samples were collected to study the mineralogical, texture, chemical composition, thermal behavior, and treatment and also the possibility to convert kaolinite mineral into metakaolin and use it as a natural pozzolanic and/or as geopolymer materials. Kaolinite is the main constituent of clay mineral, which related to many of the chemical weathering of parent rocks and complete leaching of alkali elements under warm, humid to semi-arid climatic conditions. However, quartz, anatase, and iron oxide are considered non-clay minerals. Cement substituted by metakaolin under different ratios in the concrete industry was carried out to enhance the physical and mechanical properties of the concrete. The best results are detected at 10% and 15% of cement replacement by metakaolin. Geopolymer production using Metakaolin (MK) was mixed with NaOH and Na 2 O-3SiO 2 to replace the Portland cement in the concrete industry and the obtained results are suitable and match with the green building material concept.

Secondary metabolites from Lantana camara L. flowers extract exhibit in vivo anti-urolithiatic activity in adult Wistar albino rats - Marwa I. Ezzat; Salsabeel N. El Gendy; Ahmed S. Saad; Walied S. Abdo; Aly M. EL Sayed; Amira K. Elmotayam (Natural Product Research, 2022)

The combined effect of water deficit stress and TiO2 nanoparticles on cell membrane and antioxidant enzymes in Helianthus annuus L. - Taha Ramadan; Suzan A. Sayed; Amna K. A. Abd-Elaal; Ahmed Amro (Physiology and Molecular Biology of Plants, 2022)
Nanotechnology has become one of the several approaches attempting to ameliorate the severe effect of drought on plant's production and to increase the plants tolerance against water deficit for the water economy. In this research, the effect of foliar application of TiO 2 , nanoparticles or ordinary TiO 2 , on Helianthus annuus subjected to different levels of water deficit was studied. Cell membrane injury increased by increasing the level of water deficit and TiO 2 concentration, and both types of TiO 2 affected the leaves in analogous manner. Ord-TiO 2 increased H 2 O 2 generation by 67–240% and lipid peroxidation by 4–67% in leaves. These increases were more than that induced by Nano-TiO 2 and the effect was concentration dependent. Proline significantly increased in leaves by water deficit stress, reaching at 25% field capacity (FC) to more than fivefold compared to that in plants grown on full FC. Spraying plants with water significantly decreased the activities of enzymes in the water deficit stressed roots. The water deficit stress exerted the highest magnitude of effect on the changes of cell membrane injury, MDA, proline content, and activities of CAT and GPX. Nano-TiO 2 was having the highest effect on contents of H 2 O 2 and GPX activity. In roots, the level of water deficit causes highest effect on enzyme activities, but TiO 2 influenced more on the changes of MDA and H 2 O 2 contents. GPX activity increased by 283% in leaves of plants treated with 50 and 150 ppm Nano-TiO 2 , while increased by 170% in those treated with Ord-TiO 2 , but APX and CAT activities increased by 17–197%, in average, with Ord-TiO 2 . This study concluded that Nano-TiO 2 didn’t ameliorate the effects of drought stress on H. annuus but additively increased the stress, so its use in nano-phytotechnology mustn’t be expanded without extensive studies.

Delineation and Evaluation of the Groundwater of Fractured Limestone Aquifer at East of Al Kurimat Area, Egypt: Geophysical and Hydrogeochemical Constraints - Ahmed K. Alezabawy; Alhussein Adham Basheer; El Sayed I. Selim (Pure and Applied Geophysics, 2021)

Olfactory Disturbances as Presenting Manifestation Among Egyptian Patients with COVID-19: Possible Role of Zinc - Aida A. Abdelmaksoud; Ali A. Ghweil; Mohammed H. Hassan; Alaa Rashad; Ashraf Khodeary; Zaky F. Aref; Mennatallah Ali Abdelrhman Sayed; Mahmoud K. Elsamman; Shamardan E. S. Bazeed (Biological Trace Element Research, 2021)

Role of polymeric materials in preventing COVID-19 infection - Sayed F. Abdelwahab; Mostafa K. Mohamed; Waheed Y. Ali; Ahmed S. Ali (Archives of Virology, 2021)

Metabolic resistance to organophosphate insecticides in natural populations of the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) in Egypt and molecular identification of mitotypes - El-Sayed H. Shaurub; Jorge R. Paredes-Montero; Judith K. Brown; Haggag S. Zein; Amr A. Mohamed (Phytoparasitica, 2021)

Adjuvant effect of saponin in an oil-based monovalent (serotype O) foot-and-mouth disease virus vaccine on the antibody response in guinea pigs and cattle - Abdel-Hamid I. Bazid; Hayam A. El-Alfy; Gamal El-Didamony; Wael K. Elfeil; Magdy M. El-Sayed; Mohamed Fawzy (Archives of Virology, 2021)

Risk assessment of horizontal curves using reliability analysis based on Google traffic data - Eman K. Ali; Ibrahim H. Hashim; Sayed A. Shwaly; Zaki M. Zidan; Sherif M. El-Badawy (Innovative Infrastructure Solutions, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Melatonin alleviates sepsis-induced heart injury through activating the Nrf2 pathway and inhibiting the NLRP3 inflammasome - Ibtissem Rahim; Ramy K. Sayed; Marisol Fernández-Ortiz; Paula Aranda-Martínez; Ana Guerra-Librero; José Fernández-Martínez; Iryna Rusanova; Germaine Escames; Bahia Djerdjouri; Darío Acuña-Castroviejo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Evaluation of antimicrobial properties of a novel synthesized nanometric delafossite - Mohsen A. Sayed; Asmaa A. H. El-Bassuony; H. K. Abdelsalam (Brazilian Journal of Microbiology, 2020)

Silencing of tissue factor by antisense deoxyoligonucleotide mitigates thioacetamide-induced liver injury - M. S. Abdel-Bakky; G. K. Helal; E. M. El-Sayed; A. H. Alhowail; A. M. Mansour; K. S. Alharbi; Elham Amin; S. Allam; S. A. Salama; A. S. Saad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Reproductive and developmental performance of the yellow fever mosquito, Aedes aegypti , fed on the Syrian hamster, Mesocricetus auratus , immunized with a mosquito midgut lectin - Tahany H. Ayaad; Rasha K. Al-Akeel; Ebtisam M. Al-Olayan; El-Sayed H. Shaurub; Abeer S. Aloufi (Invertebrate Reproduction & Development, 2020)

Synthesis and antiviral activity of some pyrrolonyl substituted heterocycles as additives to enhance inactivated Newcastle disease vaccine - Alaa R. I. Morsy; Sayed K. Ramadan; Mounir M. Elsafty (Medicinal Chemistry Research, 2020)

Cyclosporin A activates human hepatocellular carcinoma (HepG2 cells) proliferation: implication of EGFR-mediated ERK1/2 signaling pathway - Mohammed E. Abo-El Fetoh; Gouda K. Helal; I. G. Saleh; M. Ewees; Mohamed ElShafey; Mohamed R. Elnagar; El-Sayed Akool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Beneficial Effects of Coconut Oil in Treatment of Parkinson’s Disease - K. S. Ibrahim; E. M. El-Sayed (Neurophysiology, 2020)

Antimicrobial activity of Novel spinel nanoferrites against pathogenic fungi and bacteria - Mohsen A. Sayed; H. K. Abdelsalam; Asmaa A. H. El-Bassuony (World Journal of Microbiology and Biotechnology, 2020)

RETRACTED ARTICLE: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2019)

New antimalarial lanostane triterpenes from a new isolate of Egyptian Ganoderma species - Amir E. Wahba; Ahmed K. A. El-Sayed; Amira A. El-Falal; Eman M. Soliman (Medicinal Chemistry Research, 2019)

Comparative influence of dietary probiotic, yoghurt, and sodium butyrate on growth performance, intestinal microbiota, blood hematology, and immune response of meat-type chickens - M. N. Makled; K. F. M. Abouelezz; A. E. G. Gad-Elkareem; A. M. Sayed (Tropical Animal Health and Production, 2019)

Nutritive utilization of Moringa oleifera tree stalks treated with fungi and yeast to replace clover hay in growing lambs - K. Z. Kewan; F. A. Salem; A. Z. M. Salem; A. R. Abdou; H. M. El-Sayed; S. S. Eisa; E. A. Zaki; N. E. Odongo (Agroforestry Systems, 2019)

The molecular and biochemical insight view of lycopene in ameliorating tramadol-induced liver toxicity in a rat model: implication of oxidative stress, apoptosis, and MAPK signaling pathways - Kadry M. Sadek; Mohamed A. Lebda; Tarek K. Abouzed; Sherif M. Nasr; Yasser EL-Sayed (Environmental Science and Pollution Research, 2018)

Associative Learning of Food Odor by Social Wasps in a Natural Ecosystem - Ashraf M. El-Sayed; Júlia K. Jósvai; Robert L. Brown; Andrew Twidle; David M. Suckling (Journal of Chemical Ecology, 2018)

Does the application of silicon and Moringa seed extract reduce heavy metals toxicity in potato tubers treated with phosphate fertilizers? - Ahmed S. Elrys; Abdel-Rahman M. A. Merwad; Ahmed I. E. Abdo; Mohamed K. Abdel-Fatah; El-Sayed M. Desoky (Environmental Science and Pollution Research, 2018)

Endocrine disruption, oxidative stress, and testicular damage induced by 4-nonylphenol in Clarias gariepinus: the protective role of Cydonia oblonga - Alaa El-Din H. Sayed; Rania F. K. Ismail (Fish Physiology and Biochemistry, 2017)

Porous Inorganic Drug Delivery Systems—a Review - E. Sayed; R. Haj-Ahmad; K. Ruparelia; M. S. Arshad; M.-W. Chang; Z. Ahmad (AAPS PharmSciTech, 2017)

Synthesis and antimicrobial activity of newly synthesized 4-substituted-pyrazolo[3,4-d]pyrimidine derivatives - Ahmed M. El-Sayed; Samy M. Ibrahim; Mostafa K. Soltan; Mansour E. Abo-Kul (Medicinal Chemistry Research, 2017)

Association between IL28B rs12979860 single nucleotide polymorphism and the frequency of colonic Treg in chronically HCV-infected patients - Minesh Mehta; Helal F. Hetta; Enass A. Abdel-hameed; Susan D. Rouster; MdMonir Hossain; Mohamed A. Mekky; Nasr K. Khalil; Wegdan A. Mohamed; Mohamed A. El-Feky; Shabaan H. Ahmed; Enas A. Daef; Mohamed A. El-Mokhtar; et al. (Archives of Virology, 2016)

Experimental study on the utilization of dune sands as a construction material in the area between Jeddah and Mecca, Western Saudi Arabia - El-Sayed Sedek Abu Seif; Abdullah R. Sonbul; Bader Abdo Hasan Hakami; E. K. El-Sawy (Bulletin of Engineering Geology and the Environment, 2016)

Giardia duodenalis assemblages in Egyptian children with diarrhea - H. M. Fahmy; A. O. El-Serougi; H. K. El Deeb; H. M. Hussein; H. M. Abou-Seri; C. Klotz; T. Aebischer; K. El Sayed Khalifa Mohamed (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Occurrence of cyanobacteria and microcystin toxins in raw and treated waters of the Nile River, Egypt: implication for water treatment and human health - Zakaria A. Mohamed; Mohamed Ali Deyab; Mohamed I. Abou-Dobara; Ahmad K. El-Sayed; Wesam M. El-Raghi (Environmental Science and Pollution Research, 2015)

Rock slope stability and design in Arafat–Muzdalifa area, Saudi Arabia - Ali M. A. Abd-Allah; E. K. El-Sawy; El-Sayed Sedek Abu Seif; Abdelhamid El-Fakharani; Mohammed Amin M. Sharaf (Arabian Journal of Geosciences, 2014)

Snake (Walterinnesia aegyptia) venom-loaded silica nanoparticles induce apoptosis and growth arrest in human prostate cancer cells - Gamal Badr; Mohamed K. Al-Sadoon; Danny M. Rabah; Douaa Sayed (Apoptosis, 2013)

The role of Periodic Safety Update Reports in the safety management of biopharmaceuticals - Hans C. Ebbers; Aukje K. Mantel-Teeuwisse; Fakhredin A. Sayed-Tabatabaei; Ellen H. M. Moors; Huub Schellekens; Hubert G. M. Leufkens (European Journal of Clinical Pharmacology, 2013)

Design, synthesis, and biological activity of certain quinazolinedione derivatives as potent phosphodiestrase4 inhibitors - Afaf K. Elansary; Hanan H. Kadry; Eman M. Ahmed; Amr Sayed Motawi Sonousi (Medicinal Chemistry Research, 2012)

Design, synthesis and in vitro PDE4 inhibition activity of certain quinazolinone derivatives for treatment of asthma - Afaf K. Elansary; Hanan H. Kadry; Eman M. Ahmed; Amr Sayed Motawi Sonousi (Medicinal Chemistry Research, 2012)

Temporal and spatial distribution of dissolved Cu, Ni and Zn in the coastal waters of Jeddah, eastern Red Sea - Radwan K. Al-Farawati; Mohammad O. Gazzaz; Mohammad A. El Sayed; Amr El-Maradny (Arabian Journal of Geosciences, 2011)

In vitro and in vivo neo-cartilage formation by heterotopic chondrocytes seeded on PGA scaffolds - A. Lohan; U. Marzahn; K. El Sayed; A. Haisch; B. Kohl; R. D. Müller; W. Ertel; G. Schulze-Tanzil; T. John (Histochemistry and Cell Biology, 2011)

Molecular aspects in elevation of sunflower tolerance to drought by boron and calcium foliar sprays - Nemat M. Hassan; Ahmed K. A. El-Sayed; Heba T. Ebeid; Mamdouh M. Nemat Alla (Acta Physiologiae Plantarum, 2011)

Screening for and isolation and identification of malathion-degrading bacteria: cloning and sequencing a gene that potentially encodes the malathion-degrading enzyme, carboxylestrase in soil bacteria - Sayed K. Goda; Iman E. Elsayed; Taha A. Khodair; Walaa El-Sayed; Mervat E. Mohamed (Biodegradation, 2010)

Trail Pheromone Disruption of Red Imported Fire Ant - David M. Suckling; Lloyd D. Stringer; Barry Bunn; Ashraf M. El-Sayed; Robert K. Vander Meer (Journal of Chemical Ecology, 2010)

Bioactive lipids and antioxidant properties of wild Egyptian Pulicaria incise, Diplotaxis harra, and Avicennia marina - M. F. Ramadan; M. M. A. Amer; H. T. Mansour; K. M. Wahdan; R. M. El-Sayed; S. El-Sanhoty; W. A. El-Gleel (Journal of Consumer Protection and Food Safety, 2009)

Assessment of EST-microsatellites markers for discrimination and genetic diversity in bread and durum wheat landraces from Afghanistan - K. Chabane; O. Abdalla; H. Sayed; J. Valkoun (Genetic Resources and Crop Evolution, 2007)

Follicular dendritic cells stimulated by collagen type I develop dendrites and networks in vitro - M. E. El Shikh; R. M. El Sayed; J. G. Tew; A. K. Szakal (Cell and Tissue Research, 2007)

Assessment of EST-microsatellites markers for discrimination and genetic diversity in bread and durum wheat landraces from Afghanistan - K. Chabane; O. Abdalla; H. Sayed; J. Valkoun (Genetic Resources and Crop Evolution, 2006)

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

Isolation and characterization of two types of actinophage infectingStreptomyces scabies - El-S. A. El-Sayed; G. El-Didamony; K. Mansour (Folia Microbiologica, 2001)